Antibiotic interactions using liposomes as model lipid membranes. (August 2019) - Pinheiro, Marina; Magalhães, Joana; Reis, Salette
Highlights: Antibiotics are among the most frequently prescribed medications in modern medicine. Biophysical interaction studies constitute a platform for antibiotics development. Drug-membrane interaction studies allow to predict the ADME-Tox of new molecules. Biophysical studies permit to estalish drug'structure/membrane'activity correlation. Abstract: Lipidomics and proteomics have undergone a tremendous revolution, and the knowledge about drugs' mechanism of action in biological membranes has been deepened. Methods to study the interactions of drugs with biological membranes have opened new perspectives to rational drug design, based not only in the pharmacological target of the drugs but also on the interaction with biological membranes. These methods expand our ability to acquire the ADME-Tox profile of drugs, simplifying the complexity of biological membranes. Particularly, antibiotic resistance is considered one of the greatest threats to human health, being the prospects for replacing current antimicrobial drugs extremely scarce. With the decline of the discovery and the emergence of multidrug resistant pathogens to the existing arsenal, the objective in the development of new drugs to combat the resistance to antibiotics has been replaced by the modification of existing antibiotics. Therefore, drug-membrane interaction studies using membrane models of the eukaryotic and prokaryotic cell membranes, associated with a broad of complementary methods, may contribute to a deep picture concerning the effect of antibiotics upon their intake until their pharmacological target. This critical review will discuss the relevance of a range of different methods to study the interaction of antibiotic drugs using liposomes as biological membranes models. The advantages and the limitations of these methods will be discussed and future perspectives in this field will be proposed.